Emerging therapies for treatment of multiple sclerosis - John R Corboy (Dove Medical Press, 2010)
John R Corboy, Augusto A MiravalleRocky Mountain Multiple Sclerosis Center, Anschutz Medical Campus, University of Colorado Denver, Aurora, Colorado, USAAbstract: In the last decade, a new armamentarium of immune-based therapies have been developed and tested in patients with multiple sclerosis. Some of these therapies are showing a high level of efficacy, with an acceptable adverse effect profile. Because present therapies have significant limitations in slowing disease progression, require injections, are sometimes associated with significant side effects of immunosuppression, and do little to reverse disability, identifying more effective treatments is an important goal for clinical research in multiple sclerosis. However, in order to improve our current approach to disease-modifying therapies, it is imperative to promote the development of individualized therapy strategies.Keywords: multiple sclerosis, lymphocyte-targeted therapy, immune sequestration, non-specific immune modulation